PENGEMBANGAN MESIN PEMBUAT BRIKET BATOK KELAPA KAPASITAS 10 KG SEBAGAI UPAYA MENINGKATKAN EFISIENSI PRODUKSI PADA KELOMPOK TANI DI LALAN, KABUPATEN MUSI BANYUASIN - M. Rasid; Baiti Hidayati; Herlin Sumarna; Romli Romli; Aji Pangestu Wijaya; Labib Ghinatajaya (Politeknik Negeri Sriwijaya, Indonesia, 2025)
Charcoal briquettes are an environmentally friendly alternative energy source; however, conventional production is hampered by the slow and labor-intensive manual molding process. This study aims to improve production efficiency for farmers in Lalan, Musi Banyuasin, by designing and testing a screw-type charcoal briquette press machine powered by an electric motor. The machine is designed with a capacity of 10 kg per cycle, using coconut shell charcoal powder as the test material. The research methods include the design, fabrication, and performance testing through a comparative study of the machine and manual molding processes, as well as product uniformity evaluation. The results show a significant increase in production rate. The screw machine is able to produce an average of 24 briquettes in 50 seconds, while the manual method only produces 5 briquettes in the same time, indicating an approximately 4.8-fold increase in output. The machine's measured capacity reaches 32.29 kg/hour under extended testing conditions, and the briquettes produced are uniform according to the mold. Based on the test results, the machine demonstrates greater efficiency as the molding time increases, with a total output of 144 briquettes in 300 seconds, while the manual method only produces 30 briquettes in the same time. This study concludes that the implementation of the screw-type briquette press machine effectively accelerates the production process, reduces reliance on manual labor, and has the potential to increase the economic value of biomass waste for small- to medium-scale enterprises.